Increasing Students' Interest in Learning Fiqh through Digital Interactive Media at MTs Al-Anshor Ambon - Derlean, Najamudin (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study examines the effect of digital interactive media in increasing students' interest in learning Fiqh at Madrasah Tsanawiyah Al-Anshor, Ambon. The research design used was a quasi-experimental one, with two groups: an experimental group that utilized multimedia tools (videos, quizzes, and online discussions) and a control group that used traditional teaching methods. The results showed that the use of digital interactive media significantly increased students' engagement and academic performance in the experimental group. Students in the experimental group showed increased enthusiasm, deeper understanding of Fiqh concepts, and more active participation in lessons compared to the control group. Although the results were generally positive, there were some challenges, such as distractions caused by interactive elements. Overall, this study concludes that digital interactive media can be effective in increasing students' interest and learning outcomes in Fiqh education, and emphasizes the importance of balancing engagement and focus on content in multimedia-based learning.